Analysis of PPP1R11 expression in granulosa cells during developmental follicles of yak and its effects on cell function. Issue 1 (6th October 2022) - Min, Xingyu; Zhu, Yanjin; Hu, Yulei; Yang, Manzhen; Yu, Hailing; Xiong, Yan; Fu, Wei; Li, Jian; Matsuda, Fuko; Xiong, Xianrong
Abstract: The aims of this study were to analyse the protein phosphatase 1 regulatory subunit 11 ( PPP1R11 ) expression and cellular localization in yak follicles and investigate its effects on cell proliferation, apoptosis and oestrogen secretion in granulosa cells (GCs). Ten healthy and non‐pregnant female yaks (4‐year‐old) were used as experimental animals. The mRNA relative expression level of PPP1R11 in GCs from small (<3.0 mm), medium (3.0–5.9 mm) and large (6.0–9.0 mm) follicles was detected by RT‐qPCR, and the cellular localization of PPP1R11 protein was detected by immunohistochemistry staining (IHC). After isolation, culture and identification of yak GCs in vitro, si‐ PPP1R11 and si‐NC (negative control) were transfected into GCs. RT‐qPCR and immunofluorescence staining were used to evaluate the interference efficiency, and ELISA was performed to detect oestrogen concentration. Then, EdU staining and TUNEL staining were conducted to analyse cell proliferation and apoptosis. In addition, the oestrogen synthesis, proliferation‐ and apoptosis‐related genes were detected by RT‐qPCR after knockdown PPP1R11 . The results showed that PPP1R11 is mainly located in ovarian GCs, and the expression levels of PPP1R11 in GCs from large follicles were significantly higher than that from medium and small follicles. Transfection of si‐ PPP1R11 into GCs could significantly inhibit the expression of PPP1R11 . Interestingly, the oestrogen secretion ability and the expression level of oestrogen pathway‐related genes ( STAR, CYP11A1, CYP19A1 and HSD17B1 ) were also significantly downregulated. Moreover, the proportion of positive cells was decreased, and cellular proliferation‐related genes ( PCNA, CCNB1 and CDC25A ) were significantly downregulated after knockdown PPP1R11 . However, the proportion of apoptotic cells was increased, and apoptosis‐related genes ( BAX, CASP3 and P53 ) were significantly upregulated. Taken together, this study was the first revealed the expression and cellular localization of PPP1R11 in yak follicles. Interference PPP1R11 could reduce oestrogen secretion, inhibit proliferation and promote apoptosis in GCs, which provided a basis for further studies on the regulatory mechanism of PPP1R11 in follicle development.